STYLISTIC ANALYSIS OF ENGLISH IMPERATIVE COMMAND MOOD TRANSFER TO JAVANESE - Pinem, Yune Andryani (LLT Journal: A Journal on Language and Language Teaching, 2019)
Imperative Mood (IM) for Javanese is strongly related to social status determining language choice. Triglossia of Ngoko, Madya and Krama are pictured in language use as well as prosodic features of pitch contour. To look at how English IM transfers to Javanese is the purpose of this research as well as how this process influences variant of pitch contours produced by Javanese speaker. This is a comparative study highlighting difference and similarity visualized by Javanese and English pitch contours with similar semantic meaning to be analyzed in pragmatics stylistic framework. Imperative to Command (IC) cannot take place in Bottom-Up situation in Javanese for social reason which puts Imperative to Request (IR) and Imperative to Invite (II) as substitutions. Using sound production of Javanese from Jogja and Solo on English and Javanese imperative, intonation pattern from both languages is analyzed using PRAAT and described in pitch range. Findings of this research display cultural background of Javanese in IM which may be useful for English pronunciation class.